Handsewn Versus Stapled IPAA in Redo Setting: Indications, Patient Characteristics, Operative, Functional, and Quality-of-Life Outcomes. Issue 8 (26th April 2021) - Esen, Eren; Erkan, Arman; Aytac, Erman; Esterow, Joanna; Grieco, Michael J.; Kirat, Hasan T.; Remzi, Feza H.
Abstract : BACKGROUND : The impact of the type of anastomosis on the outcomes of redo IPAA is unknown. OBJECTIVE: The aim of this study is to assess the indications, perioperative outcomes, and functional outcomes in patients undergoing stapled vs handsewn redo IPAA. DESIGN: This is a retrospective cohort study. SETTINGS: This investigation is based on a single academic practice group experience with redo IPAA. PATIENTS: Patients who underwent redo IPAA for ileal pouch failure between September 2016 and May 2020 were included in the study. MAIN OUTCOME MEASURES: Indications, perioperative outcomes, functional outcomes, restrictions, and quality-of-life scores were compared between stapled and handsewn groups. RESULTS: A total of 105 patients underwent redo IPAA for ileal pouch failure of whom 76 (72%) had handsewn and 29 (28%) had stapled reanastomosis. The interval between the index and redo IPAA was shorter in stapled redo IPAA (median (interquartile range), Stapled: 3 years (1–4) vs handsewn: 7 years (3–17), p < 0.001). Handsewn anastomosis was more commonly used after pelvic sepsis (handsewn: n = 57 (76%) vs stapled: n = 13 (45%), p = 0.002). Overall postoperative morbidity was similar between the 2 groups (handsewn: n = 38 (50%) vs stapled: n = 16 (55%), p = 0.635). The number of bowel movements, pad use, daily restrictions, and Cleveland Global Quality of Life scores were similar between stapled and handsewn groups. Although daytime seepage was more common after handsewn anastomosis (handsewn, n = 20 (44%) vs stapled, n = 3 (14%), p = 0.013), nighttime seepage was similar in both groups. Pouch survival rates were comparable: 88% vs 92% (p > 0.05). LIMITATIONS: This study is limited by its low study power and limited follow-up time. CONCLUSIONS: Patients who had pelvic sepsis after their index IPAA required handsewn anastomosis at higher rates than other redo cases. Although handsewn anastomosis is a more complex procedure, it is associated with morbidity, functional outcomes, and quality-of-life scores similar to stapled anastomosis for redo IPAA. See Video Abstract at http://links.lww.com/DCR/B580 . RECONSTRUCCIÓN DE ANASTOMOSIS ILEONAL CON RESERVORIO ILEAL CON SUTURA MANUAL VERSUS ANASTOMOSIS CON ENGRAPADO: INDICACIONES, CARACTERÍSTICAS DEL PACIENTE, RESULTADOS OPERATORIOS, FUNCIONALES Y DE CALIDAD DE VIDA: ANTECEDENTES: Se desconoce el impacto en los resultados del tipo de anastomosis se rehace una anastomosis ileonal con reservorio ileal (IPAA). OBJETIVO: El propósito de este estudio es evaluar las indicaciones, resultados perioperatorios y funcionales en pacientes sometidos a una reconstrucción IPAA con engrapado vs sutura manual. DISEÑO: Este es un estudio de cohorte retrospectivo. ENTORNO CLINICO: Esta investigación se basa en la experiencia de un solo grupo de práctica académica sobre reconstrucción IPAA . PACIENTES: Se incluyeron en el estudio pacientes que fueron sometidos a una reconstrucción de IPAA por falla del reservorio ileal entre septiembre del 2016 hasta mayo del 2020. PRINCIPALES MEDIDAS DE VALORACION: se compararon indicaciones, resultados perioperatorios, funcionales, restricciones y puntuaciones de calidad de vida entre los grupos de engrapado y sutura manual. RESULTADOS: Un total de 105 pacientes fueron sometidos a una reconstrucción de IPAA por falla del reservorio ileal, de los cuales 76 (72%) fueron reanastomosis con sutura manual y 29 (28%) con engrapado. El intervalo entre la cirugía inicial y la reintervención de IPAA fue más corto en la reconstrucción de IPAA con engrapado [mediana ( IQR ), engrapado: 3 años (1-4) vs con sutura manual: 7 años (3-17), p <0, 001]. La anastomosis con sutura manual se realizo con mayor frecuencia después de sepsis pélvica [sutura manual: n = 57 (76%) vs engrapado: n = 13 (45%), p = 0, 002]. La morbilidad postoperatoria total fue similar entre los dos grupos [sutura manual: n = 38 (50%) vs engrapado: n = 16 (55%), p = 0, 635]. El número de evacuaciones intestinales, el uso de paños protectores, restricciones diarias y puntuaciones en CGQL fueron similares entre los grupos de engrapado y sutura manual. Si bien el manchado por la mañana fue más común después de la anastomosis con sutura manual [sutura manual, n = 20 (44%) vs engrapado, n = 3 (14%), p = 0.013], el manchado por la noche fue similar en ambos grupos. Las tasas de sobrevida con reservorio fueron comparables; 88% vs 92% respectivamente ( p > 0, 05). LIMITACIONES: Este estudio está limitado por su bajo poder de estudio y su tiempo de seguimiento limitado. CONCLUSIONES: Los pacientes que tuvieron sepsis pélvica después de su primer IPAA, requirieron anastomosis con sutura manual en un porcentaje más alto que otros procedimientos de reintervención. Si bien es cierto, la anastomosis con sutura manual es un procedimiento mucho más complejo; este se asoció a una morbilidad, resultados funcionales y puntuaciones de calidad de vida similares en comparación a la anastomosis con engrapado cuando se rehace la IPAA . Consulte Video Resumen en http://links.lww.com/DCR/B580 . (Traducción— Dr. Francisco M. Abarca-Rendon )